2011
DOI: 10.3389/fpsyg.2011.00176
|View full text |Cite
|
Sign up to set email alerts
|

Facilitated Auditory Detection for Speech Sounds

Abstract: If it is well known that knowledge facilitates higher cognitive functions, such as visual and auditory word recognition, little is known about the influence of knowledge on detection, particularly in the auditory modality. Our study tested the influence of phonological and lexical knowledge on auditory detection. Words, pseudo-words, and complex non-phonological sounds, energetically matched as closely as possible, were presented at a range of presentation levels from sub-threshold to clearly audible. The part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…Finally, the results of the present study showed that lexical processing could be observed for stimuli that are not behaviorally categorized, but partially detected. Although the choice of a lexical task as a measure of awareness is largely accepted in studies investigating linguistic processing without awareness (for reviews, see Kouider et al ., ; Van den Bussche et al ., ), further research would be required to assess whether lexical processing could also occur in experimental conditions involving a detection task, as recently suggested in a behavioral study showing lexical processing without subjective detection (Signoret et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Finally, the results of the present study showed that lexical processing could be observed for stimuli that are not behaviorally categorized, but partially detected. Although the choice of a lexical task as a measure of awareness is largely accepted in studies investigating linguistic processing without awareness (for reviews, see Kouider et al ., ; Van den Bussche et al ., ), further research would be required to assess whether lexical processing could also occur in experimental conditions involving a detection task, as recently suggested in a behavioral study showing lexical processing without subjective detection (Signoret et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…This result is in accordance with studies done in the visual modality suggesting that the lexical or semantic processing can occur without awareness (for a meta‐analysis, see Van den Bussche et al ., ). This result is also in accordance with behavioral studies done in the auditory modality showing lexical processing without awareness (Daltrozzo et al ., ; Signoret et al ., ), and suggests that lexical processing is concomitant with a variation of low‐beta (15–20 Hz) power near the left temporal regions, independently of any awareness of the category of the stimulus.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations